Effects of Giving Education on Covid-19 Prevention By Using Visual Audio On Adolescents’ Knowledge - Triana Indrayani; Endes Novi Ismawati; Anni Suciawati (Universitas STRADA Indonesia, 2021)
This pre-experimental research design used a one-group pre-test-post-test design. Using the purposive sampling technique, the sample in this study was 58 respondents who are residents of Sukakarya Village, Megamendung District, Bogor. The data were analyzed using the paired sample t-test which was previously tested for normality. Univariate analysis of adolescents' knowledge on the prevention of COVID-19 through audiovisuals obtained an average value of 25.57 and an average post-test score of 30.83. Meanwhile, the bivariate analysis showed the effects of providing education on COVID-19 prevention by using audiovisuals on adolescents' knowledge with a significance value of 0.000. Audiovisual media affect adolescents' knowledge on COVID-19 prevention. It is hoped that adolescents can increase their COVID-19 prevention knowledge by using video media so that they can change their behavior in efforts to prevent COVID-19 transmission